A Study on Architecture of Kerala Temples: Exploring the Unique Architectural Features of Kerala Temples (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper exhibits quite certain examination into architectural character of Kerala temples. For this reason, distinctive parts of plan and height of Kerala temple are investigated compared with Dravida style. The development of temple architecture in Kerala is arranged under three stages. The examination draws a reasonable picture of Kerala temples inside the expansive region of Dravida style. The explanations for plan of the interesting type of architecture which break from dreary Dravida style are the versatility to local condition, utilization of various building materials and methods utilized by manufacturers as per the materials.